Global Issues and Research Trends On Science Learning Based On The Scopus Database From 2019 To 2023: A Bibliometric Analysis - Jayanti, Mei Indra; Umar, Umar; Syarifuddin, Syarifuddin (Faculty of Mathematics and Natural Sciences, Universitas Negeri Yogyakarta, 2024)
Previous research tends to examine science learning in general, but less focus on specific sub-topics, such as inquiry-based learning, project-based learning, or STEAM approaches. The research aims to map the trend of research development related to science learning. There are 987 metadata of Scopus-indexed journal articles from 2019 to 2024. They are analyzed bibliometrically using VOSviewer software combined with the R program and Biblioshiny to find trends in science learning research. The results revealed the development of science learning research from 2019 to 2024. The highest number of Scopus-indexed in 2022 reached 228 publication articles (23.10%). Huwer J's position is the most productive author in science learning research with eight published articles. Journal of Education Sciences is the top scientific journal with 56 articles published on the topic of science learning. Michigan State University occupies the first rank as the higher education institution that publishes the most science learning research topics with 36 relevant articles. Science learning research with the topic